PENGARUH KOMPENSASI, BUDAYA ORGANISASI, MOTIVASI DAN KINERJA PEGAWAI - Sanusi Sanusi; Nurwati Nurwati; Wahuniati Wahyuniati (Pascasarjana Universitas Halu Oleo, 2019)
The purpose of this study was to examine and explain the effect of compensation, organizational culture, and motivation on employee performance. Data collection is done using survey methods through questionnaires and interviews. The population of this study is the Hati Mulia Hospital in Kendari City, amounting to 80 people. Because the population in this study is relatively small, all the populations in the study were made as respondents. The analytical tool used is Multiple Linear Regression Analysis. The results showed that simultaneous compensation, organizational culture, and motivation had a positive and significant effect. Then partially compensation has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance; motivation has a positive and not significant effect on employee performance.Keywords: compensation, organizational culture, motivation, employee performance